ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI PEMILIHAN MODA WISATAWAN MANCANEGARA DI KAWASAN KUTA RAYA - Wicaksana, Ngurah Putu Bayu Pinasthika; Yori Herwangi (Jurnal Teknik Sipil dan Arsitektur, 2026)
Kuta Raya is one of Bali’s main tourist destinations, characterized by high mobility among international tourists and various transportation mode options. This study aims to analyze the factors related to international tourists’ preferences in choosing transportation modes in the Kuta Raya area. Data were collected through questionnaires distributed to 134 international tourists visiting Kuta, Seminyak, and Legian. The analysis employed the Crosstab method with the Chi-Square (?²) test to identify statistical relationships between tourist characteristics, travel factors, and mode choice. The results indicate that driving license ownership (SIM A), frequency of visit, transportation cost, and parking cost have a significant relationship (p < 0.05) with tourists’ mode choice. Meanwhile, variables such as gender, age, income, and comfort show no significant relationship. These findings suggest that cost-related aspects and travel experience are the main considerations influencing international tourists’ transportation mode preferences in the Kuta Raya area.